ART, CULTURE, AND TECHNOLOGY: RESEARCH PROCESSES FOR INTELLECTUAL VALUE CREATION AND SUSTAINABILITY IN THE AI ERA - Pastraporn Thipayasothorn (International Journal of Industrial Education and Technology, 2025)
This article presents an integrated research approach between "art, culture, and technology" to create intellectual value and sustainability in the era of artificial intelligence (AI). The focus is on conceptual analysis and theoretical frameworks, not empirical experimentation. In the 21st century, technology has become a key factor profoundly transforming human learning and creativity. Therefore, art and culture serve not only as a foundation of identity but also as "cultural-intellectual capital" that can be transformed into knowledge and social value. Thipayasothorn et al. (2024, p. 112) demonstrate that the use of technology in cultural community development projects, such as the "Water Catchment Area - Water Conservation in the East of Bangkok," can tangibly enhance collaborative learning and social sustainability. Furthermore, AI plays a role as a "co-creator," helping to process, analyze, and create new knowledge from artistic and cultural data. The research processes for creating intellectual value thus encompasses exploration, integration, innovation, and reflection. Under the framework of three theoretical concepts: Cultural Capital Theory, Sociotechnical Systems Theory, and Human–AI Co-Creation Theory, which reflect the "three-dimensional balance" of art, culture, and technology, this article concludes that such integrated research is a key mechanism for creating "collaborative intelligence" that promotes the sustainability of human society in the AI era.
Keywords: Innovation, Sustainability, Human-Machine Systems; University-Industry-Government Innovation Models; Earth Systems and Cosmic Evolution